PENGARUH BUDAYA ORGANISASI, LINGKUNGAN KERJA, DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA PEGAWAI PT BANK PEMBANGUNAN DAERAH BANTEN KANTOR PUSAT DUTA INDAH ICONIC - Muhamad Alif Ashari (2022)
The purpose of this study was to determine whether there is an influence of organizational culture, work environment, and career development variables on job satisfaction of employees of PT Bank Pembangunan Daerah Banten Head Office of Duta Indah Iconic. This research is quantitative research with primary data sources. The object of this research is staff-level employees at Bank Banten with a sample of 112 respondents using a simple random sampling technique as sampling technique. Descriptive and inferential data analysis techniques. Based on the results of data processing through t-statistics on Smart PLS, it is intended that organizational culture has a significant positive effect on job satisfaction, with an original sample value of 0.457 and a significance value of 0.000. the work environment has a significant positive effect on job satisfaction, with the original sample value of 0.190 and a significance value of 0.019. Career development has a significant positive effect on job satisfaction, with an original sample value of 0.313 and a significance value of 0.000. From the results of these studies, Bank Banten should be able to improve existing values, make employees comfortable, implement a healthy environment and create appropriate career development programs in order to achieve job satisfaction.